Salidroside promotes sciatic nerve regeneration following combined application epimysium conduit and Schwann cells in rats. Issue 6 (March 2020) - Li, Jiaqi; Zhang, Yongguang; Yang, Zhimin; Zhang, Jingxian; Lin, Ren; Luo, Daoshu
Schwann cell and nerve conduit are crucial for nerve regeneration and re-myelination after peripheral nerves injury. To investigate the effects of Salidroside on autogenous epimysium conduit mixed with BD matrigel and RSC96 Schwann cells on an animal model with 5 mm sciatic nerve defect injury in rat, motor function, muscle reinnervation, immunohistochemical staining, retrograded tracing and Western blot were used in this study. The results showed that Salidroside enhanced the compound effects of epimysium conduit mixed with BD matrigel and RSC96 Schwann cells to improve the sciatic functional index and the gastrocnemius muscle weight ratio, which were better than EPM group at 8 weeks and 12 weeks post operation. Immunofluorescence and Western blot results of P75 NTR showed that Salidroside improved the sciatic nerve regeneration, and retrograded tracing of CTB-Alexa 488 also supported that Salidroside was better to promote CTB tracer transporting from the distal nerve defect to the ipsilateral dorsal root ganglion and ventral horn of L3-L5 spinal cord on post-operation 8 weeks and 12 weeks. Our results demonstrated that Salidroside improved the effect of autogenous epimysium conduit mixed with BD matrigel and RSC96 Schwann cells on sciatic nerve regeneration in our study. Impact statement: Peripheral nerve injury and regeneration remain a major challenge. Although nerve conduit and Schwann cells have been used to study the nerve regeneration, our results demonstrated that Salidroside improved the regenerative effect in a rat model with sciatic nerve injury model, following a combined application of autogenous epimysium conduit mixed with Schwann cells. Different concentrations of Salidroside combining autogenous epimysium conduit and Schwann cells were applied to compare the epimysium conduit group and the epimysium conduit combining Schwann cells group. Based on the results of motor function and muscle reinnervation evaluation, as well as neuronal tracing and expression of P75 NTR, our study for the first time suggests that Salidroside may improve the regeneration effect on the sciatic nerve following a combined application of epimysium conduit and RSC96 Schwann cells in rats.